Mineralogy and petrology of Yamato 000593: Comparison with other Martian nakhlite meteorites - Mikouchi,Takashi; Koizumi,Eisuke; Monkawa,Akira; Ueda,Yuji; Miyamoto,Masamichi (National Institute of Polar Research, 2003)
P(論文) Yamato (Y) 000593 is a new nakhlite recovered from Antarctica and is composed of roughly 80% augite, 10% olivine and 10% mesostasis. Augite is chemically homogeneous except for Fe-rich rims adjacent to the mesostasis. Olivine has more extensive chemical zoning, but the most Fe-rich part is also near the mesostasis. These observations suggest that chemical zoning of both augite and olivine was produced by interaction with the mesostasis. The crystallization history of Y000593 as deduced from this study is as follows. (1) Crystallization of cumulus augite and olivine and formation of symplectites in olivine. (2) Accumulation of augite and olivine. (3) Mesostasis crystallization and interaction of the augite and olivine rims with the intercumulus melt. (4) Aqueous alteration. The petrography and mineralogy of Y000593 is generally similar to other nakhlites, but minor mineralogical differences are observed. These differences resulted from different thermal histories due to different locations (burial depths) in the same cooling cumulate pile. Y000593 is most similar to Nakhla and both samples experienced similar formation histories. However, later mesostasis crystallization of Y000593 was more rapid than Nakhla due to its faster cooling rate. The burial depth of Y000593 would be shallower than 3 m from the surface, and is intermediate between NWA817 and Nakhla. The abundance and mineralogy of the mesostasis as well as augite and olivine rim compositions are related to the burial depths of nakhlites. departmental bulletin paper